Exploring the stigma against people with mental illness in Bangladesh - Prodyut Roy; Kamal Uddin Ahmed Chowdhury (Cambridge Prisms: Global Mental Health, 2024)
This study investigates the stigma against people with mental illness in Bangladesh through in-depth interviews with 14 patients and 9 healthcare professionals, and 33 focus group discussions with people without mental illness. The research has delved into the understanding of different types of stigma against mental illness in the context of Bangladesh. The findings revealed four types of stigma which were categorized into four themes namely self-stigma, public stigma, professional, and institutional stigma. Patients had internalized negative attitudes, thereby discriminated toward themselves. The public discriminated against patients because of believing in prejudices against them. Other health professionals had negative conceptions toward patients, and they devalued mental health professionals (MHPs). A culture of negative attitude and belief had emerged in institutional settings which encouraged discrimination. Policymakers and healthcare professionals can use the findings to develop a mental health service by addressing the stigma. Mental health practitioners can assess the impact of stigma to improve the mental well-being of their patients. Students and workplace staff will benefit from intentional or unintentional discrimination in educational institutions and workplace settings by addressing the effects of stigma. Importantly, other health care providers will be aware of their thoughts against patients and MHPs.